2021
DOI: 10.3390/nu13020538
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Pilot Study of DASH Patterned Groceries on Serum Urate in Individuals with Gout

Abstract: The Dietary Approaches to Stop Hypertension (DASH) diet reduces serum urate (SU); however, the impact of the DASH diet has not been previously evaluated among patients with gout. We conducted a randomized, controlled, crossover pilot study to test the effects of ~$105/week ($15/day) of dietitian-directed groceries (DDG), patterned after the DASH diet, on SU, compared with self-directed grocery shopping (SDG). Participants had gout and were not taking urate lowering therapy. Each intervention period lasted 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…There is also a strong emphasis on limiting the consumption of sodium, sugar and saturated fats [24].This dietary pattern among many health benefits is associated not only with the lower risk of gout as prospective cohort study conducted on men investigated [25], but its benefits were also observed among patients who already have gout and were at a time not during pharmacological urate lowering therapy (ULT). The outcome suggested that this strategy may be a useful tool to lower the urate serum level [26].This evidence is also supported by another study which compared a dash diet to standard diet and one with higher vegetables and fruits consumption, but without other restriction. Dash diet turned out to be the most beneficial in reducing serum urate levels [27].…”
Section: Dash Diet In the Treatment Of Goutmentioning
confidence: 60%
“…There is also a strong emphasis on limiting the consumption of sodium, sugar and saturated fats [24].This dietary pattern among many health benefits is associated not only with the lower risk of gout as prospective cohort study conducted on men investigated [25], but its benefits were also observed among patients who already have gout and were at a time not during pharmacological urate lowering therapy (ULT). The outcome suggested that this strategy may be a useful tool to lower the urate serum level [26].This evidence is also supported by another study which compared a dash diet to standard diet and one with higher vegetables and fruits consumption, but without other restriction. Dash diet turned out to be the most beneficial in reducing serum urate levels [27].…”
Section: Dash Diet In the Treatment Of Goutmentioning
confidence: 60%
“…Cherries were considered to be a good source of dietary K, which played an important role in the Dietary Approaches to Stop Hypertension (DASH), and could reduce blood pressure and stroke risk ( 1 ), as well as lowering serum urate among gout patients ( 36 ). In the accessions, the contents of K ranged from 250.906 to 453.887 mg/100 g FW, much higher than the records in the USDA MyPyramid nutrient data 173 and 222 mg/100 g FW at sour and sweet cherries respectively ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these cultivars showed lower values of chrome (C) and hue angle (H), corresponding to a darker and more intense color. The differences among sour cherry cultivars in fruit color may also underline the variability in the accumulation pattern of specific anthocyanin molecules ( 14), the larger the number of hydroxyl groups on the B-ring, the bluer the color (35). And as pH increase, the color of anthocyanin moves to the non-spectral purple and approaches a progressive loss of fruit color.…”
Section: The Color Traits Of the Sour Cherry Accessionsmentioning
confidence: 99%
“…Recent pilot studies suggest that dietitian-directed diet modification may lower SUA concentrations and gout flares in people with gout. 24,25 However, previous studies, not involving dietitians, have demonstrated that providing general dietary education compared with specific dietary recommendations for gout to people already on ULT does not affect SUA concentrations. 26 Such uncertainty surrounding diet interventions could, in part, also account for the reported lack of referrals from GPs to dietitians specifically for gout.…”
Section: Discussionmentioning
confidence: 99%